Perceptions of educational professionals regarding the goals and implementation of the school cluster system reform in Namibia: a case study of one cluster in Caprivi region: 1999-2011 - Tembwe, Nicolars Nyambe (School of Education, 2015)
The School Cluster System (SCS) reform was introduced in Namibia from 1996 under the auspices of the Basic Education Project. The SCS entails the organising of schools into groups for educational, management and administrative purposes. In the framework of the SCS policy schools are grouped according to their geographical proximity and the curriculum they offer in order to work together as a collective network, one school in the group being selected as the core school, or Cluster Centre. There are varying goals for the promotion of the SCS policy depending on context, but close examination of the international literature reveals that the most widespread arguments for this policy are based on assumptions that a SCS seeks to enhance education quality through localised decision-making, interschool cooperation and community participation in education. One of the key assumptions of the SCS reform is that it seeks to achieve cost-effectiveness by allowing schools to pool educational resources. The focus on the SCS policy in the last two decades, in particular in the developing countries, appears to be closely linked to the ongoing efforts of achieving the internationally set goals of the 1990 World Declaration on Education for All (EFA) within a context of financial austerity. In this study, the purpose was to investigate how educational professionals perceive and understand the goals and the implementation of the SCS policy in the Caprivi region of Namibia. The study aimed to explore the views and experiences of the case study participants regarding the effectiveness of the SCS in relation to the goals of decentralized management and local support for rural schools. The study examines the views and experiences of implementers of the SCS in a rural context, including the challenges faced by the implementers in the process of implementation.